Penerapan Edukasi Kesehatan untuk Mencegah Penyakit Tidak Menular di Desa Lokki, Kabupaten Seram Bagian Barat - Sherly Lewerissa; Angeline Ch. Wattimena; Yuliana S. A. Napitupulu; Lorraine J. Aipassa; Chriscellia F. P. Lerebulan (Yayasan Literasi Sains Indonesia, 2025)
Non-communicable diseases (NCDs) are diseases that occur not due to infection but are diseases that are not transmitted from person to person. This is because PTM is the most common cause of death in the world at 74%. KKN students in Lokki Village, carried out a free health check-up work program including Socialization on Non-Communicable Diseases, checking blood pressure, uric acid, cholesterol and blood sugar, with the participation of 76 people from adults to the elderly with the aim of so that the prevalence rate of non-communicable disease cases can decrease in the Lokki Village community. This program was implemented on November 7 2024 at the Lokki Village Saniri Hall to carry out socialization and at the Teratai Community Health Center (PUSTU) to carry out examinations and counseling. The methods used are socialization, physical examination and counseling. The results of this activity obtained blood pressure above normal (hypertension) by 39.4%, high blood sugar (hyperglycemia) by 5.9%, high uric acid examination (hyperuresemia) by 33.3%, and high cholesterol (hypercholesterolemia) by 9.2% of the 76 people who participated. Based on this data, routine checks are needed to control and prevent the high number of non-communicable diseases in Lokki Village.